Charge transfer at organic/inorganic interfaces and the formation of space charge regions studied with infrared light - Beck, Sebastian; Gerbert, David; Glaser, Tobias; Pucci, Annemarie (The journal of physical chemistry. C, Energy, materials, and catalysis, 2015)
We present in situ infrared spectroscopy as a powerful tool for the qualitative and quantitative analysis of the charge transfer through the prototypical interface between the organic semiconductor 4,4′-bis(N-carbazolyl)-1,1′-biphenyl (CBP) and MoO3 that in organic electronic devices is often used to improve their performance. Due to the different infrared vibrational spectra, charged and neutral species of CBP molecules can be well distinguished, which allows the measurement of the amount of charged species in the vicinity of the interface. The quantitative analysis of CBP thickness-dependent infrared transmission spectra delivered the extension of the space charge region from the interface into the CBP on a nanometer scale. The clear influence of the deposition sequence on these interface properties was clarified by further studies of the inverted layer structures.